Self-supporting film based on intermetallic PtCu nanowire cluster and preparation method and application thereof
By preparing a self-supporting film based on the intermetallic PtCu nanowire cluster, the problems of slow oxygen reduction reaction, high catalyst cost and short life of traditional carbon-loaded electrodes in hydrogen fuel cells are solved, and more efficient and stable electrochemical performance and lower production costs are achieved.
Patent Information
- Application Number
- CN202510624830.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-15
- Publication Date
- 2025-06-13
- Estimated Expiration
- 2045-05-15
AI Technical Summary
In the prior art, traditional carbon-loaded electrodes face many challenges in the industrialization of hydrogen fuel cells due to problems such as slow oxygen reduction reaction, high catalyst cost and short life.
The self-supporting film based on intermetallic PtCu nanowire clusters was prepared by solvent-thermal synthesis method and solvent evaporation-induced self-assembly process, combined with SiO2 protective layer cladding and domain-limited heat treatment, and a catalytic layer with open pores, flexibility and mechanical strength was formed.
It improves the output power and performance of hydrogen fuel cells and has stable output, enhances the structural stability and electrochemical activity of the catalyst, and reduces production costs and complexity.
Smart Images

Figure CN120149438A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hydrogen fuel cell catalysis, and particularly relates to an intermetallic PtCu nanowire cluster self-supporting film, a preparation method thereof and an application thereof. Background Art
[0002] Proton exchange membrane fuel cells belong to clean and sustainable energy conversion technologies. However, due to the slow oxygen reduction reaction (ORR) of traditional carbon-supported electrodes, their industrialization still faces problems such as too high catalyst costs (the usage amount of precious metal platinum > 0.2 mg / cm 2 ) and short service life. Therefore, as a complex system involving electrocatalytic reactions, charge migration and mass transfer, it is very important to measure the enhancement and balance of the electrochemical process from different dimensions, understand the construction of the electrode structure, and form an effective "solid-liquid-gas" three-phase transport channel to drive the sustainable progress of the cathode ORR.
[0003] Platinum, as the most effective ORR catalyst, the structure and morphology controllable preparation, electronic structure regulation and the structure-activity relationship between the electrochemical properties based on thin film glassy carbon electrodes have been widely studied. Recently reported intermetallic catalysts, the periodic and ordered arrangement of platinum atoms and transition metal atoms makes the intermetallic compounds have stronger 3d-5d orbital interactions and electronic effects, thereby enhancing the ORR activity and stability. In addition, nano-based metal films with large-scale ordered arrangement structures constructed based on high aspect ratio nanowires will bring new properties or enhanced performances to electrode catalytic materials. Currently, most catalysts are in powder form. In order to evaluate the electrochemical properties of a three-electrode system, the catalyst powder is usually mixed with a conductive carbon material, and the highly conductive glassy carbon substrate eliminates the influence of the electrode resistivity on the electrochemical properties. Moreover, the electrolyte proton concentration in the three-electrode system is sufficient, greatly weakening the influence of the proton transport limitation on the electrochemical properties. Optimizing the electrode catalytic layer structure can effectively achieve high catalyst utilization rate and enhance the gas / liquid transport performance in the actual membrane electrode assembly. Traditionally, the catalytic layer is prepared by methods such as coating the catalyst on a gas diffusion layer electrode or coating the catalyst on a membrane. Due to its dense and disordered structure, it leads to low gas / liquid mass transfer efficiency and insufficient catalyst utilization rate; high potential carbon carrier corrosion causes the pore structure and skeleton of the catalytic layer to collapse; the discontinuous proton transport network limits the effective transport of protons in the cathode catalytic layer; and the two-dimensional interface structure of the traditional membrane electrode results in poor mass transfer and stability at the interface between the cathode catalytic layer and the proton exchange membrane.
[0004] To avoid these problems, researchers are committed to binder-free self-supporting electrodes: ordered arrays, nano-porous metal ordered carrier thin films, electrospun fiber membranes, PS, SiO 2 、K 2 CO 3Such as template-packed electrodes. Among them, the electrospun fiber membrane electrode process is suitable for mass production. However, using polymer fibers as the support and after carbonization treatment, the membrane has poor mechanical strength and flexibility, and extremely strong hydrophobicity, which is not suitable for constructing the reaction three-phase interface. The template-packed electrode can effectively construct a multi-scale pore structure electrode, but the preparation process is complex and the pore structure is prone to collapse. The nano-porous metal thin film prepared by the dealloying method has a double continuity of ligaments and pores in its structure, which is beneficial to the orderly transport of electrons and protons.
[0005] Patent CN117476960A discloses a nano-porous Pt thin film, its preparation method and application in fuel cell electrodes. The prepared Pt thin film has high electrocatalytic activity. When applied to fuel cell electrodes, it can improve the battery output power and stable performance output. Ordered carrier arrays such as CNTs, nickel foam, metal oxides, etc. are most commonly used because of their porous structure, easy availability and low cost. The catalytically active substance is directly sprayed / grown on the ordered substrate. However, there are still some problems in the actual later applications: the preparation process of the CNT array is relatively complex and not suitable for mass production; the conductivity of the metal oxide array is poor; the cathode prepared with a conductive polymer as an ordered carrier faces serious flooding, etc. Therefore, traditional porous metal electrodes have limitations, and self-supporting electrodes are difficult to apply under harsh conditions.
[0006] Nano-wires, nano-tubes, nano-rods, etc. prepared by methods such as solvothermal reduction are sprayed to prepare an ultra-thin catalytic layer, the thickness, composition and pore size of which are controllable and adjustable. However, the connection between the nano-wires, nano-tubes and nano-rods is only a simple physical superposition contact, which is not conducive to the transport of protons between the nano-wires in the catalytic layer, and thus affects the efficient transport and distribution of protons between and within the planes. Therefore, although the catalytic layer composed of nano-wires, tubes and rods has excellent electrochemical performance and excellent mass transport performance brought by the open structure, its battery performance is always poor. Summary of the Invention
[0007] The technical problem to be solved by the present invention is to overcome the above-mentioned defects existing in the prior art, and provide a self-supporting thin film based on intermetallic PtCu nanowire clusters, which has excellent open pores, flexibility and mechanical strength. The present invention also provides a preparation method thereof, with mild preparation conditions and a simple process. Applying the self-supporting thin film of intermetallic PtCu nanowire clusters prepared by the present invention to fuel cells can improve the battery output power and stable performance output.
[0008] The preparation method of the self-supporting thin film based on intermetallic PtCu nanowire clusters of the present invention includes the following steps: preparing a metal salt precursor solution → obtaining a PtCu alloy nanowire cluster catalyst → obtaining a self-supporting PtCu nanowire cluster thin film → preparing a surface-coated SiO 2Self-supporting PtCu nanowire cluster thin film of the protective layer → Intermetallic PtCu nanowire cluster self-supporting thin film is prepared; The preparation of the surface-coated SiO 2 Self-supporting PtCu nanowire cluster thin film of the protective layer, the specific steps are: Immerse the self-supporting PtCu nanowire cluster thin film in tetraethyl orthosilicate and formic acid solution to coat SiO on its surface 2 Coating layer, and then dry to obtain a self-supporting PtCu nanowire cluster thin film with a surface-coated SiO 2 Protective layer; The volume ratio of tetraethyl orthosilicate to formic acid is 1-10, the impregnation temperature is 40-60 °C, and the impregnation time is 2-6 h.
[0009] The preparation of the intermetallic PtCu nanowire cluster self-supporting thin film, the specific steps are: Place the self-supporting PtCu nanowire cluster thin film with a surface-coated SiO 2 Protective layer in a reducing atmosphere for heat treatment, the heat treatment temperature is 400-800 °C, and the heat treatment time is 2-10 h to obtain an intermetallic PtCu nanowire cluster self-supporting thin film. The reducing atmosphere is 5% H 2 / N 2 (volume ratio).
[0010] The specific steps for preparing the metal salt precursor solution are: Dissolve platinum and copper precursors in water to prepare a precursor solution with a concentration of 50-200 mmol / L, then add a reducing agent, a structure-directing agent, and an organic solvent, adjust the pH of the solution to 10-14, control the atomic ratio of platinum to copper to 1:1, and stir until a clear, transparent, and homogeneous metal salt precursor solution is formed. The precursors are chloroplatinic acid, potassium chloroplatinate, copper chloride, and copper nitrate. Potassium hydroxide is used to adjust the pH.
[0011] The reducing agent is glucose, urea, ascorbic acid, or sodium citrate; the structure-directing agent is N,N-dimethylformamide, dimethylacetamide, N-methylpyrrolidone, ethylenediamine, or hexamethylphosphoric triamide; the organic solvent is ethylene glycol, glycerol, 1,3-propanediol, propylene glycol, diethylene glycol, or methanol.
[0012] The added mass of the reducing agent is 50 wt-200 wt% of platinum and palladium, the added volume of the structure-directing agent is 2-10 mL, the added volume of the organic solvent is 4-12 mL, and the total added volume of the structure-directing agent and the organic solvent is 10%-50% of the total volume of the reaction kettle. The organic solvent, as the solvent main body and the structure-directing agent, has a much larger added volume and is usually not calculated by mass ratio.
[0013] The specific steps for preparing the PtCu alloy nanowire cluster catalyst are as follows: Heat and keep the metal salt precursor solution warm to form a black colloidal solution precipitate, add a solvent and centrifuge to obtain the PtCu alloy nanowire cluster catalyst. Heat to 140 - 200 °C and keep warm for 6 - 12 h. The solvent is absolute ethanol, and centrifuge and wash 3 - 5 times.
[0014] The specific steps for preparing the self - supported PtCu nanowire cluster thin film are as follows: Add the PtCu alloy nanowire cluster catalyst to ethanol and disperse it by ultrasonic treatment for 0.5 - 4 h until a black and homogeneous suspension with a concentration of 0.4 - 5 mg / mL is formed, and then perform vacuum evaporation to obtain the self - supported PtCu nanowire cluster thin film; the vacuum evaporation temperature is 30 - 60 °C, and the evaporation time is 24 - 48 h.
[0015] An intermetallic PtCu nanowire cluster self - supported thin film is prepared by the preparation method of the intermetallic PtCu nanowire cluster self - supported thin film described above.
[0016] Transfer the intermetallic PtCu nanowire cluster self - supported thin film to a mica sheet or a PET substrate, and use the hot - pressing method to transfer the intermetallic PtCu nanowire cluster self - supported thin film from the substrate surface to the Nafion membrane surface and assemble it into a hydrogen fuel cell.
[0017] Specifically, the preparation method of the intermetallic PtCu nanowire cluster self - supported thin film includes the following steps: (1) Dissolve platinum and copper precursors in water to prepare a precursor solution with a concentration of 50 - 200 mmol / L, add a reducing agent, a structure - directing agent, and a solvent, adjust the pH to 10 - 14, control the atomic ratio of platinum to copper to be 1:1, and stir magnetically to form a clear, transparent, and homogeneous metal salt precursor solution; (2) Transfer the metal salt precursor solution to a 25 - mL reaction kettle, heat it in an oven to 140 - 200 °C, keep it warm for 6 - 12 h, and a black colloidal solution precipitate is formed at the bottom of the solvothermal kettle. Centrifuge it with an ethanol solution 3 - 5 times, collect the above - mentioned black colloidal catalyst, and obtain a PtCu alloy nanowire cluster catalyst with a Pt / Cu atomic ratio of 1:1; (3) Prepare the self - supported PtCu nanowire cluster thin film by the solvent evaporation - induced self - assembly process. Disperse the PtCu nanowire cluster catalyst prepared in step (2) in ethanol, ultrasonically disperse it for 0.5 - 4 h until a black and homogeneous suspension is formed with a concentration of 0.4 - 5 mg / mL. Then pour 0.5 mL - 10 mL of the catalyst suspension into a polytetrafluoroethylene mold with a bottom area of 1 - 4 cm 2 Slowly evaporate the solvent in a 30 - 60 °C vacuum oven for 24 - 48 h to obtain the self - supported PtCu nanowire cluster thin film; (4) The self-supporting PtCu nanowire cluster thin film is immersed in a solution of tetraethyl orthosilicate (TEOS) and formic acid with a volume ratio of 1 to 10 at 40 to 60 °C for 2 to 6 h to coat a layer of SiO 2 coating layer on its surface, and then dried in a vacuum oven for 12 h to obtain a self-supporting PtCu nanowire cluster thin film with a SiO 2 protective layer on its surface; (5) The self-supporting SiO 2 coated layer PtCu nanowire cluster thin film obtained in step (4) is placed in a tubular furnace with a reducing atmosphere of 5% H 2 / N 2 and heat-treated at 400 to 800 °C for 2 to 10 h to obtain an intermetallic PtCu nanowire cluster self-supporting thin film.
[0018] Specifically, the intermetallic PtCu nanowire cluster self-supporting thin film is first subjected to an electrochemical test: The self-supporting intermetallic PtCu thin film material is cut into circular pieces with a diameter of 4 mm and placed on a glassy carbon electrode coated with a 0.5 wt% Nafion membrane solution on the surface. Nitrogen is used to blow dry the surface of the electrode covered with the thin film to fix the thin film, obtaining a glassy carbon electrode with the self-supporting intermetallic PtCu thin film, and then an electrochemical test of a three-electrode system is carried out to characterize the electrochemical active area and oxygen reduction performance of the thin film material.
[0019] Specifically, the application of the intermetallic PtCu nanowire cluster self-supporting thin film in a hydrogen fuel cell electrode: The intermetallic PtCu nanowire cluster self-supporting thin film is transferred onto a mica sheet or a PET substrate. By using a hot pressing method, with a pressure of 2 to 15 MPa, a temperature of 50 to 200 °C, and a time of 0.5 to 10 min, the intermetallic PtCu nanowire cluster self-supporting thin film is transferred from the substrate surface to the Nafion membrane surface and assembled into a hydrogen fuel cell fixture for single cell performance testing.
[0020] For the intermetallic PtCu nanowire cluster self-supporting thin film described in the present invention, first, a PtCu alloy nanowire cluster with a Pt / Cu atomic ratio of 1:1 is prepared by a solvothermal synthesis method. By using a structure-directing agent, the PtCu nanowires form nanowire clusters according to the oriented attachment mechanism. Then, it is ultrasonicated and dispersed in ethanol to form a catalyst slurry, and the PtCu nanowire clusters are induced to stack by the slow evaporation of the ethanol solution to form a self-supporting thin film material with a certain area. By using the TEOS solution method and formic acid to adjust the solution pH, silicic acid molecules react with the TiO 2 surface hydroxyl groups to generate continuous SiO 2The membrane uniformly coats the surface of the PtCu nanowire clusters as a protective layer, confines the coarsening during the heat treatment of the PtCu nanowire clusters, and finally uses the confined thermal effect to be treated in a reducing atmosphere to induce the diffusion and rearrangement of Cu and Pt atoms to grow into a chemically ordered structure, preparing an intermetallic PtCu nanowire cluster self-supporting film with adjustable pore size and thickness and certain flexibility and mechanical strength. The intermetallic PtCu is a face-centered cubic ordered intermetallic compound.
[0021] Aiming at the problems in the prior art that porous metal thin films are applied to self-supporting electrodes of hydrogen fuel cells, such as the easy corrosion, dissolution, shedding and agglomeration of metal-based oxygen reduction electrocatalysts in acidic media, resulting in high cost, low activity and poor stability of the catalysts. The porous thin film electrode formed by the interpenetrating and overlapping of the intermetallic PtCu nanowire clusters prepared in the present invention has an adjustable catalytic layer loading and thickness, an easily adjustable pore size, a strong binding force with the proton exchange membrane, and a small interfacial resistivity. The method has a wide application range and is used in the field of electrocatalysis of self-supporting thin film electrodes of hydrogen fuel cells to improve the battery output power and stable output performance.
[0022] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) Using the intermetallic PtCu nanowire cluster self-supporting film prepared by the present invention, the Pt loading of the catalyst is controllable, the thickness is uniform, the pore size is easily adjustable, the binding force with the Nafion membrane is strong, and the interfacial resistance is small. The intermetallic PtCu nanowire cluster self-supporting film has an area (such as 1×1 cm 2 , 2×2 cm 2 , 5×5 cm 2 dimensions) that can be customized according to requirements, meeting the actual application requirements of the electrodes of fuel cells.
[0023] (2) Using the intermetallic PtCu nanowire cluster self-supporting film prepared by the present invention, the intermetallic PtCu nanowire clusters therein have a high aspect ratio, and the film formed by their interpenetration has open pores, flexibility and mechanical strength; it has a fixed stoichiometric ratio and a highly ordered atomic structure, and the Pt and Cu metal atoms are combined with each other through strong d-d orbital interactions, which can inhibit the dissolution of non-precious metals and improve the structural stability of the catalyst.
[0024] (3) The preparation method of the intermetallic PtCu nanowire cluster self-supporting film of the present invention uses non-precious metal Cu as a doping atom, and combines the solvothermal synthesis method, the solvent evaporation-induced self-assembly process and the confined heat treatment method to prepare the intermetallic PtCu nanowire cluster self-supporting film, which has the characteristics of low cost, environmental friendliness, simple steps and mild preparation conditions.
[0025] (4)The self-supported film of intermetallic PtCu nanowire clusters prepared by the present invention is not only applicable to electrochemical catalytic half-reactions, but can also be directly applied to the membrane electrode of a fuel cell as a self-supported electrode to improve the output power and stable output performance of the cell. Description of the Drawings
[0026] Figure 1 It is a transmission electron microscope image of the microscopic morphology of the self-supported film of intermetallic PtCu nanowire clusters prepared in Example 1.
[0027] Figure 2 It is a scanning electron microscope image of the microscopic morphology of the self-supported film of intermetallic PtCu nanowire clusters prepared in Example 1.
[0028] Figure 3 It is an XRD spectrum of the self-supported PtCu nanowire cluster film (disordered) obtained in step (3) and the self-supported film of intermetallic PtCu nanowire clusters (ordered) obtained after step (5) in Example 1.
[0029] Figure 4 It is a BET nitrogen adsorption-desorption curve of the self-supported film of intermetallic PtCu nanowire clusters prepared in Example 1.
[0030] Figure 5 It is a cyclic voltammogram curve at the initial stage and after 3000 cycles in the electrochemical test in Application 1.
[0031] Figure 6 It is an oxygen reduction polarization curve at the initial state and after 3000 cycles in the electrochemical test in Application 1.
[0032] Figure 7 It is a polarization curve of the hydrogen / air fuel cell prepared in Application 2 at 30 °C, 60 °C, and 80 °C.
[0033] Figure 8 It is a scanning electron microscope image of the microscopic morphology of the film prepared in Comparative Example 1. Detailed Embodiments
[0034] The present invention will be further described below in conjunction with specific embodiments.
[0035] The raw materials and auxiliaries used in the following examples and comparative examples are all commercially available products. Copper chloride is calculated based on anhydrous copper chloride, with a molecular weight of 135. Chloroplatinic acid is hexahydrate chloroplatinic acid, and the molecular weight is calculated according to 518. The Nafion membrane is a proton exchange membrane from DuPont.
[0036] Example 1 The preparation method of the self-supported film based on intermetallic PtCu nanowire clusters includes the following steps: (1) Dissolve 0.518 g of chloroplatinic acid and 0.135 g of copper chloride in 20 mL of water respectively to prepare a precursor solution with a concentration of 50 mmol / L. Add 6 mL of ethylene glycol and 4 mL of N,N-dimethylformamide, and adjust the pH to 10 with potassium hydroxide. Magnetically stir to form a clear, transparent and homogeneous metal salt precursor solution; (2) Each time, take 0.2 mL of the metal salt precursor solution and perform multiple preparations according to the following steps: Transfer it to a 25 mL reaction kettle, heat it in an oven to 170 °C, and keep it warm for 8 h. A black colloidal solution precipitate is formed at the bottom of the solvothermal kettle. Centrifuge it 3 times with an ethanol solution, and collect the black colloidal catalysts obtained multiple times to obtain a PtCu alloy nanowire cluster catalyst with a Pt / Cu atomic ratio of 1:1; (3) Prepare a self-supporting PtCu nanowire cluster thin film by the solvent evaporation-induced self-assembly process. Disperse 10 mg of the PtCu alloy nanowire cluster catalyst prepared in step (2) into 25 mL of ethanol, and ultrasonically disperse it for 0.5 h until a black homogeneous suspension is formed with a concentration of 0.4 mg / mL. Then pour 0.5 mL of the catalyst suspension into a polytetrafluoroethylene mold with a bottom area of 1×1 cm 2 Evaporate ethanol in a vacuum oven at 30 °C for 48 h to obtain a self-supporting PtCu nanowire cluster thin film; (4) Immerse 0.2 mg of the self-supporting PtCu nanowire cluster thin film in TEOS and formic acid with a volume ratio of 2 at 40 °C for 6 h to completely impregnate it, so that a SiO 2 coating layer is formed on its surface. Then dry it in a vacuum oven for 12 h to obtain a self-supporting PtCu nanowire cluster thin film with a SiO 2 protective layer on its surface; (5) Place the self-supporting PtCu nanowire cluster thin film with a SiO 2 protective layer obtained in step (4) in a tubular furnace with a reducing atmosphere of 5% (volume ratio) H 2 / N 2 Heat-treat it at 600 °C for 4 h to obtain a self-supporting thin film of intermetallic PtCu nanowire clusters.
[0037] The transmission electron microscopy image of the microstructure of the prepared self-supporting thin film of intermetallic PtCu nanowire clusters is as shown in Figure 1 It can be seen that it is composed of metal nanowire clusters. The scanning electron microscopy image of the microstructure of the prepared self-supporting thin film of intermetallic PtCu nanowire clusters is as shown in Figure 2As shown, it shows a nanowire cluster structural unit with a high aspect ratio of 300 - 400 nm. The self-supporting film constructed has an open pore structure, an exact Pt / Cu atomic ratio (1:1), a high porosity, has a certain flexibility, and can be separated from the mold without damage to its integrity, demonstrating that the film has a certain mechanical strength. The XRD pattern of the prepared intermetallic PtCu nanowire cluster self-supporting film is as Figure 3 the ordered pattern. The self-supporting PtCu nanowire cluster film obtained after step (3) is disordered, as shown in Figure 3 the disordered pattern in Figure 3 It can be seen that the disordered PtCu nanowire cluster film maintains the face-centered cubic (fcc) structure of the Pt crystal (ICDD standard powder diffraction PDF database PDF#04 - 0802). The XRD diffraction peaks of the heat-treated PtCu (ordered) match well with the intermetallic PtCu structure (ICDD standard powder diffraction PDF database PDF#42 - 1326). The BET nitrogen adsorption - desorption isotherm curve of the prepared intermetallic PtCu nanowire cluster self-supporting film is as Figure 4 shown. BET pore size analysis shows that the large surface area (about 90 m 2 / g), high porosity of 76%, and two concentrated bands of pore size distribution of 20 - 60 nm and 60 nm - 300 nm of the PtCu nanowire cluster assembly construct a large electrochemically accessible surface area and a fast mass transfer flux, which can significantly improve the electrocatalytic performance.
[0038] Example 2 The preparation method of the intermetallic PtCu nanowire cluster self-supporting film described above includes the following steps: (1) Dissolve 1.036 g of chloroplatinic acid and 0.27 g of copper chloride in 20 mL of water respectively to prepare a precursor solution with a concentration of 100 mmol / L. Add 0.31 g of glucose, 5 mL of dimethylacetamide, 7 mL of glycerol, and add potassium hydroxide to adjust the pH to 11. Stir magnetically to form a clear, transparent and homogeneous metal salt precursor solution; (2) Take 0.1 mL of the metal salt precursor solution each time and perform multiple preparations according to the following steps: Transfer it to a 25 mL reaction kettle, heat it in an oven to 140 °C, keep it warm for 12 h, and a black colloidal solution precipitate forms at the bottom of the solvothermal kettle. Centrifuge it with an ethanol solution 3 times, and collect the black colloidal catalysts obtained multiple times to obtain a PtCu alloy nanowire cluster catalyst with a Pt / Cu atomic ratio of 1:1; (3) Prepare a self - supported PtCu nanowire cluster thin film by a solvent evaporation - induced self - assembly process. Disperse 10 mg of the PtCu alloy nanowire cluster catalyst prepared in step (2) into 20 mL of ethanol, and ultrasonically disperse for 2 h until a black and homogeneous suspension is formed with a concentration of 0.5 mg / mL. Then pour 6.4 mL of the catalyst suspension into a polytetrafluoroethylene mold with a bottom area of 2×2 cm 2 and evaporate ethanol in a vacuum oven at 40℃ for 48 h to obtain a self - supported PtCu nanowire cluster thin film; (4) Immerse 3.2 mg of the self - supported PtCu nanowire cluster thin film completely in a mixture of TEOS and formic acid with a volume ratio of 5 at 60℃ for 2 h to coat a SiO 2 coating layer on its surface, and then dry it in a vacuum oven for 12 h to obtain a self - supported PtCu nanowire cluster thin film with a SiO 2 protective layer on its surface; (5) Place the self - supported PtCu nanowire cluster thin film with a SiO 2 protective layer obtained in step (4) into a tubular furnace with a reducing atmosphere of 5% (volume ratio) H 2 / N 2 and heat - treat at 400℃ for 10 h to obtain an intermetallic PtCu nanowire cluster self - supported thin film.
[0039] Example 3 The preparation method of the intermetallic PtCu nanowire cluster self - supported thin film described above includes the following steps: (1) Dissolve 1.036 g of chloroplatinic acid and 0.27 g of copper chloride in 20 mL of water respectively to prepare a precursor solution with a concentration of 100 mmol / L. Add 0.31 g of urea, 5 mL of N - methylpyrrolidone, and 6 mL of 1,3 - propanediol, and adjust the pH to 12 with potassium hydroxide, and magnetically stir to form a clear, transparent, and homogeneous metal salt precursor solution; (2) Each time take 0.1 mL of the metal salt precursor solution and perform multiple preparations according to the following steps: Transfer it to a 25 - mL reaction kettle, heat in an oven to 200℃, keep warm for 6 h, and a black colloidal solution precipitate is formed at the bottom of the solvothermal kettle. Centrifuge with an ethanol solution 3 times, and collect the black colloidal catalysts obtained multiple times to obtain a PtCu alloy nanowire cluster catalyst with a Pt / Cu atomic ratio of 1:1; (3) Prepare a self - supported PtCu nanowire cluster thin film by a solvent evaporation - induced self - assembly process. Disperse 10 mg of the PtCu alloy nanowire cluster catalyst prepared in step (2) into 20 mL of ethanol, and ultrasonically disperse for 3 h until a black and homogeneous suspension is formed with a concentration of 0.5 mg / mL. Then pour 4 mL of the catalyst suspension into a polytetrafluoroethylene mold with a bottom area of 2×2 cm 2In a polytetrafluoroethylene mold, the solvent ethanol was evaporated in a vacuum oven at 60 °C for 24 h to obtain a self-supporting PtCu nanowire cluster film; (4) Place 2 mg of the self-supporting PtCu nanowire cluster film in TEOS and formic acid with a volume ratio of 10 and completely immerse it at 45 °C for 4 h to coat a layer of SiO 2 coating layer on its surface, and then dry it in a vacuum oven for 12 h to obtain a self-supporting PtCu nanowire cluster film with a SiO 2 protective layer on its surface; (5) Place the self-supporting PtCu nanowire cluster film with a SiO 2 protective layer obtained in step (4) in a tubular furnace with a reducing atmosphere of 5% (volume ratio) H 2 / N 2 and heat-treat it at 500 °C for 8 h to obtain an intermetallic PtCu nanowire cluster self-supporting film.
[0040] Example 4 The preparation method of the intermetallic PtCu nanowire cluster self-supporting film described above includes the following steps: (1) Dissolve 1.554 g of chloroplatinic acid and 0.405 g of copper chloride in 20 mL of water respectively to prepare a precursor solution with a concentration of 150 mmol / L. Add 0.54 g of sodium citrate, 4 mL of N,N-dimethylformamide, and 6 mL of ethylene glycol. Add potassium hydroxide to adjust the pH to 13 and stir magnetically to form a clear, transparent, and homogeneous metal salt precursor solution; (2) Each time, take 0.067 mL of the metal salt precursor solution and perform multiple preparations according to the following steps: Transfer it to a 25 mL reaction kettle, heat it in an oven to 180 °C, keep it warm for 9 h, and a black colloidal solution precipitate is formed at the bottom of the solvothermal kettle. Centrifuge it with an ethanol solution 5 times, and collect the black colloidal catalysts obtained multiple times to obtain a PtCu alloy nanowire cluster catalyst with a Pt / Cu atomic ratio of 1:1; (3) Use the solvent evaporation-induced self-assembly process to prepare a self-supporting PtCu nanowire cluster film. Disperse 10 mg of the PtCu alloy nanowire cluster catalyst prepared in step (2) in 5 mL of ethanol, ultrasonically disperse it for 4 h until a black homogeneous suspension is formed with a concentration of 2 mg / mL. Then pour 4.5 mL of the catalyst suspension into a polytetrafluoroethylene mold with a bottom area of 3×3 cm 2 and evaporate the solvent ethanol in a vacuum oven at 30 °C for 48 h to obtain a self-supporting PtCu nanowire cluster film; (4) Place 9 mg of the self-supporting PtCu nanowire cluster film in TEOS and formic acid with a volume ratio of 6 and completely immerse it at 50 °C for 5 h to coat a layer of SiO 2 coating layer on its surface, and then dry it in a vacuum oven for 12 h to obtain a self-supporting PtCu nanowire cluster film with a SiO2 Self-supporting PtCu nanowire cluster thin film of the protective layer; (5) Place the self-supporting PtCu nanowire cluster thin film with the protective layer obtained in step (4) into a tubular furnace with a reducing atmosphere of 5% (volume ratio) H 2 Self-supporting PtCu nanowire cluster thin film of the protective layer, and heat-treat it at 700 °C for 5 h in a tubular furnace with a reducing atmosphere of 5% (volume ratio) H 2 / N 2 to obtain an intermetallic PtCu nanowire cluster self-supporting thin film.
[0041] Example 5 The preparation method of the intermetallic PtCu nanowire cluster self-supporting thin film described above includes the following steps: (1) Dissolve 1.036 g of chloroplatinic acid and 0.27 g of copper chloride in 10 mL of water respectively to prepare a precursor solution with a concentration of 200 mmol / L. Add 0.31 g of ascorbic acid, 4 mL of N,N-dimethylformamide, and 8 mL of ethylene glycol, and adjust the pH to 14 with potassium hydroxide. Stir magnetically to form a clear, transparent, and homogeneous metal salt precursor solution; (2) Take 0.1 mL of the metal salt precursor solution each time and perform multiple preparations according to the following steps: Transfer it to a 25 mL reaction kettle, heat it in an oven to 160 °C, and keep it warm for 9 h. A black colloidal solution precipitate is formed at the bottom of the solvothermal kettle. Centrifuge it 5 times with an ethanol solution, and collect the black colloidal catalysts obtained multiple times to obtain a PtCu alloy nanowire cluster catalyst with a Pt / Cu atomic ratio of 1:1; (3) Prepare a self-supporting PtCu nanowire cluster thin film by a solvent evaporation-induced self-assembly process. Disperse 10 mg of the PtCu alloy nanowire cluster catalyst prepared in step (2) in 20 mL of ethanol, and ultrasonically disperse it for 1 h to form a black homogeneous suspension with a concentration of 0.5 mg / mL. Then pour 12.8 mL of the catalyst suspension into a polytetrafluoroethylene mold with a bottom area of 4×4 cm 2 Evaporate the solvent ethanol in a 40 °C vacuum oven for 24 h to obtain a self-supporting PtCu nanowire cluster thin film; (4) Place 6.4 mg of the self-supporting PtCu nanowire cluster thin film in TEOS and formic acid with a volume ratio of 1 and completely immerse it at 60 °C for 2 h to coat a SiO 2 coating layer on its surface, and then dry it in a vacuum oven for 12 h to obtain a self-supporting PtCu nanowire cluster thin film with a SiO 2 protective layer; (5) Place the self-supporting PtCu nanowire cluster thin film with the SiO 2 protective layer obtained in step (4) into a tubular furnace with a reducing atmosphere of 5% (volume ratio) H 2 / N 2In a tubular furnace with a reducing atmosphere, heat treatment is carried out at 600 °C for 3 h to obtain a self-supporting film of intermetallic PtCu nanowire clusters.
[0042] Comparative Example 1 This comparative example is the same as Example 1, except that step (4) is removed, and in step (5), only "Place the self-supporting PtCu nanowire cluster film in a tubular furnace with a reducing atmosphere of 5% H 2 / N 2 and heat-treat at 600 °C for 4 h". The results show that during the heat treatment of the intermetallic PtCu nanowire clusters without the SiO 2 surface coating layer, severe agglomeration occurred in the nanostructure morphology of the nanowire clusters, reducing the electrochemically active area, and the pore size and porosity of the pore structure decreased significantly, further hindering the mass transfer during the electrocatalytic process. The scanning electron micrograph of its structural morphology is as Figure 8 shown.
[0043] Comparative Example 2 This comparative example is the same as Example 1, except that step (3) is removed. With the same parameters for other steps, the final results show that for the film prepared without the solvent evaporation-induced self-assembly process, the nanowire cluster unit structures are arranged loosely and cannot form a self-supporting film with certain flexibility and mechanical strength, thus affecting the testing of the glassy carbon three-electrode system and the membrane electrode system and reducing the battery performance.
[0044] Comparative Example 3 This comparative example is the same as Example 1, and in step (5), the heat treatment process is modified to heat-treat at 380 °C for 4 h in a tubular furnace with a reducing atmosphere of 5% H 2 / N 2 . With all other steps being the same, the results show that heat treatment at a temperature below 400 °C cannot cause the transformation of PtCu nanowire clusters from an atomic disordered state to an ordered structure, accelerating the structurally destructive dissolution of Cu atoms in the catalyst in an acidic electrolyte system, thus being unfavorable for the performance of film stability.
[0045] Comparative Example 4 This comparative example is the same as Example 1, and in step (2), the solvothermal synthesis process is modified to heat in an oven to 130 °C and keep warm for 12 h. The results show that at a synthesis temperature below 140 °C, even if the synthesis reaction time is extended, nanowire clusters constructed by ultrafine nanowire units cannot be formed, and there is obvious particle accumulation, which is not conducive to the preparation of a self-supporting film with flexibility and mechanical strength.
[0046] Prepare the films obtained in the above Examples 1 to 5 and Comparative Examples 1 to 4 into supported film electrodes, and conduct Application 1 and Application 2 experiments. The specific preparation method is as shown in the following steps: (1) The self-supported film of intermetallic PtCu nanowire clusters was respectively cut into two shapes: a circle with an area of 0.1256 cm 2 (applied to a glassy carbon electrode with Φ4 mm) and a square with 1 cm 2 (applied to a membrane electrode of a battery with 1 cm×1 cm). The film cut into a circle with an area of 0.1256 cm 2 was covered on the surface-cleaned glassy carbon electrode, fixed with Nafion solution, dried at room temperature, and subjected to subsequent electrochemical three-electrode system tests.
[0047] (2) The film cut into a square with 1 cm 2 was transferred to a proton exchange membrane by hot pressing to obtain a square electrode with 1 cm 2 , and subsequent membrane electrode tests of the fuel cell system were carried out.
[0048] Application 1: Electrochemical tests were carried out using the self-supported film of intermetallic PtCu nanowire clusters prepared in Example 1: Cyclic voltammetry characterization was performed. A three-electrode system was composed of a glassy carbon electrode with the film catalyst as the working electrode, a saturated calomel electrode as the reference electrode, and a carbon rod electrode as the counter electrode. Using N 2 -saturated 0.1 mol / L -1 HClO 4 as the electrolyte solution, the cyclic voltammetry technique was selected on the electrochemical workstation, and cyclic scanning tests were carried out at a scanning speed of 50 mV / s -1 in the potential range of -0.24 - 0.9 V vs SCE. The cyclic voltammograms in the initial state and after 3000 cycles are as Figure 5 shown. It can be seen that the nanowire cluster film exhibits obvious hydrogen absorption / desorption peaks, indicating the existence of an ordered surface atomic structure. The electrochemical active area (ECSA) of the film in the present invention was estimated by integrating the charge amount of the hydrogen absorption / desorption process to be 51.8 m 2 / g, and after 3000 accelerated stability cycle tests, the ECSA of the intermetallic PtCu nanowire cluster film only lost 8%. The oxygen reduction polarization curves in the initial state and after 3000 cycles are as Figure 6 shown. From Figure 6 it can be seen that the limiting current of the curve after cycling decreases and the current density corresponding to 0.9 V decreases significantly, demonstrating good intrinsic activity stability. Therefore, the above tests show that the structure of the self-supported film has significant advantages in the oxygen reduction reaction.
[0049] Application 2: The application of the self-supporting intermetallic PtCu nanowire cluster thin film prepared in Example 1 in a fuel cell electrode was subjected to hydrogen-oxygen fuel cell performance testing. The intermetallic PtCu nanowire cluster thin film transferred to the Nafion 211 membrane by hot pressing was used as the cathode, and the catalyst loading was 0.2 mg / cm 2 , which was placed between the prepared anode and cathode electrodes to form a sandwich structure. Under a pressure of 0.75 MPa, it was hot pressed on a hot press at 135 °C. The hot pressing was carried out with positive pressure and negative pressure, each for 90 s, to obtain a membrane electrode with an area of 1 cm 2 . During the single-cell performance test, after connecting the membrane electrode, gas pipelines, and pressure devices, first, humidified high-purity N 2 was introduced into the anode and cathode of the cell to discharge the impurity gases in the cell. The gas flow rate was 200 mL / min -1 , and it was continuously introduced into the cell for 50 min. Then, back pressures of 0.5 bar and 1.5 bar required for the anode and cathode during the cell test were applied to the cell. Then, humidified high-purity H 2 and air were introduced into the anode and cathode sides respectively, with a flow rate of 200 mL / min -1 . Then, the fuel cell test system was used to complete the test of the I-V curve of the cell performance under specified temperature and conditions. The polarization curves of the prepared hydrogen / air fuel cell at 30 °C, 60 °C, and 80 °C are shown in Figure 7 . The I-V curve showed a normal open-circuit voltage of 0.95 - 0.98 V, indicating that the self-supporting thin film cathode catalyst layer had good impedance hydrogen permeability and good oxygen reduction performance. Test conditions: The anode electrode was a commercially purchased 0.1 mg Pt / cm -2 Pt / C (40 wt%) electrode. At temperatures of 30 °C, 60 °C, and 80 °C, and a back pressure of 1.5 bar, the peak power densities reached 232 mW / cm -2 , 407 mW / cm -2 and 615 mW / cm -2 respectively. After cyclic scanning 5000 times in the voltage range of 0.6 - 1 V, the peak power density of the cell under the condition of 60 °C only decreased by 5%, showing good hydrogen fuel cell performance overall.
[0050] The self-supporting nanowire cluster thin films prepared in the above examples and comparative examples were subjected to detection of the electrochemically active area, retention rate after cycling, peak power density of the membrane electrode, and stability performance during accelerated testing according to standards such as catalyst loading, nanowire cluster size, and porosity. The detection results are shown in Table 1.
[0051] Table 1 Detection Results
[0052] The results of Example 1 and Comparative Example 1 show that, on the premise that other conditions are the same, without SiO 2 coating on the intermetallic PtCu nanowire clusters, during the heat treatment process, the structural morphology of the nanowire clusters underwent severe agglomeration. The scanning electron microscopy images are as shown in Figure 8 , which reduced the electrochemically active area. The pore size and porosity of the pore structure decreased significantly, further hindering the mass transfer during the electrocatalytic process. The SiO 2 coating acts as a nanoreactor to promote the transformation from disorder to order and can also serve as a scaffold to mitigate the degradation of nanostructures. The results of Example 1 and Comparative Example 2 show that for the thin film prepared without the solvent evaporation-induced self-assembly process, the unit structure of the nanowire clusters is arranged loosely and cannot provide a self-supporting film with certain flexibility and mechanical strength, making it impossible to construct an interpenetrating pore and catalyst skeleton structure during the electrochemical and membrane electrode tests, resulting in poor stability. The results of Example 1 and Comparative Example 3 show that after reducing the heat treatment temperature under the reducing atmosphere, the transformation of the PtCu nanowire clusters from an atomic disordered structure to an ordered structure cannot be achieved, indicating that high-temperature heat treatment provides energy to overcome the activation energy, enabling the atomic directional migration to specific positions to form an ordered structure, thus leading to low stability. The results of Example 1 and Comparative Example 4 show that after reducing the temperature of the solvothermal synthesis, the nanowire cluster structure composed of ultrafine nanowires cannot be successfully prepared. Most of the prepared thin films are composed of particle accumulation, showing low open porosity and low activity and stability when applied to electrochemistry and membrane electrodes.
Claims
1. A method for preparing a self-supporting film based on intermetallic PtCu nanowire clusters, characterized in that: The following steps are involved: Prepare metal salt precursor solution → prepare PtCu alloy nanowire cluster catalyst → prepare self-supporting PtCu nanowire cluster film → prepare self-supporting PtCu nanowire cluster film with SiO2 protective layer on the surface → prepare intermetallic PtCu nanowire cluster self-supporting film; The preparation of the self-supporting PtCu nanowire cluster film with a surface coated with a SiO2 protective layer comprises the following specific steps: immersing the self-supporting PtCu nanowire cluster film in a solution of ethyl orthosilicate and formic acid to coat the surface with a SiO2 coating layer, and then drying to obtain a self-supporting PtCu nanowire cluster film with a surface coated with a SiO2 protective layer; The method for preparing the intermetallic PtCu nanowire cluster self-supporting film comprises the following specific steps: subjecting the self-supporting PtCu nanowire cluster film with a surface coated with a SiO2 protective layer to heat treatment in a reducing atmosphere at a heat treatment temperature of 400-800°C to obtain the intermetallic PtCu nanowire cluster self-supporting film.
2. The method for preparing a self-supporting film based on intermetallic PtCu nanowire clusters according to claim 1, characterized in that: The specific steps for preparing the metal salt precursor solution are: dissolving platinum and copper precursors in water to obtain a precursor solution with a concentration of 50-200 mmol / L, then adding a structure directing agent and an organic solvent, adjusting the solution pH to 10-14, and stirring until a clear, transparent and uniform metal salt precursor solution is formed.
3. The method for preparing a self-supporting film based on intermetallic PtCu nanowire clusters according to claim 2, characterized in that: A structure directing agent, an organic solvent and a reducing agent are added to the precursor solution, and then the pH of the solution is adjusted.
4. The method for preparing a self-supporting film based on intermetallic PtCu nanowire clusters according to claim 3, characterized in that: The structure directing agent is N,N-dimethylformamide, dimethylacetamide, N-methylpyrrolidone, ethylenediamine or hexamethylphosphoric triamide; the organic solvent is ethylene glycol, glycerol, 1,3-propylene glycol, propylene glycol, diethylene glycol or methanol; the reducing agent is glucose, urea, ascorbic acid or sodium citrate.
5. The method for preparing a self-supporting film based on intermetallic PtCu nanowire clusters according to claim 1, characterized in that: The specific steps of preparing the PtCu alloy nanowire cluster catalyst are: heating and keeping the metal salt precursor solution to generate a black colloidal solution precipitate, adding a solvent and centrifuging to obtain the PtCu alloy nanowire cluster catalyst.
6. The method for preparing a self-supporting film based on intermetallic PtCu nanowire clusters according to claim 5, characterized in that: Heat to 140~200℃ and keep warm for 6~12h.
7. The method for preparing a self-supporting film based on intermetallic PtCu nanowire clusters according to claim 1, characterized in that: The specific steps for preparing the self-supporting PtCu nanowire cluster film are as follows: adding the PtCu alloy nanowire cluster catalyst to ethanol for ultrasonic dispersion to form a black uniform suspension, and vacuum evaporating to obtain the self-supporting PtCu nanowire cluster film; the vacuum evaporation temperature is 30~60℃, and the evaporation time is 24~48h.
8. The method for preparing a self-supporting film based on intermetallic PtCu nanowire clusters according to claim 1, characterized in that: The volume ratio of ethyl orthosilicate to formic acid is 1~10, the immersion temperature is 40~60℃, and the immersion time is 2~6h.
9. A self-supporting film based on intermetallic PtCu nanowire clusters, characterized in that The invention is prepared by the preparation method of the intermetallic PtCu nanowire cluster self-supporting film according to any one of claims 1 to 8.
10. An application of the self-supporting film based on intermetallic PtCu nanowire clusters according to claim 9, characterized in that: The intermetallic PtCu nanowire cluster self-supporting film is transferred to a mica sheet or a PET substrate, and the intermetallic PtCu nanowire cluster self-supporting film is transferred from the substrate surface to the Nafion membrane surface by hot pressing and assembled into a hydrogen fuel cell fixture.
Citation Information
Patent Citations
Platinum-based intermetallic nanocrystalline oxygen reduction catalyst and preparation method thereof
CN110783584A
Platinum-copper alloy nanowire as well as preparation method thereof and application thereof
CN111313045A
Self-supporting hard carbon negative electrode with high surface capacity and preparation and application thereof
CN112993247A
SiO2 layer coated carbon nanotube loaded Pt-based alloy catalyst as well as preparation method and application thereof
CN117936823A
PtCu alloy catalyst with one-dimensional nanowire structure as well as preparation method and application of PtCu alloy catalyst
CN118577802A
Cited By
Nano microstructure color leather and preparation method thereof
CN121428189A